Modeling the energy consumption of a lift - Ahmed, Shamsuddin Shahnawaz; Iqbal, Asif P M; Sarwar, Rashed; Salam, Dr. Md. Sayeed (© 2014 Elsevier B.V., 2016)
This article was published in the Energy and Buildings [© 2014 Elsevier B.V.] and the definite version is available at: http://doi.org/10.1016/j.enbuild.2013.12.005 The Article's website is at: http://www.sciencedirect.com/science/article/pii/S0378778813008116